PENGEMBANGAN WEBSITE TERHADAP PERENCANAAN KARIER DI SMPN 1 PADALARANG - Riska Diana Putri; Euis Eti Rohaeti; Riesa Rismawati Siddik (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
One of the tasks of adolescent development is to develop talent, interest and plan a career. But in the field not all students have good career planning and can develop their talents and interests. Based on this, it is necessary to have a solution to optimize student development tasks. One of them can use career information services through the website. The subjects of this study were class VIII students with a limited-scale research sample of 10 students, and a large-scale research sample of 35 students. This research uses the development research method or RnD (Research and Development). This study aims to determine the effectiveness of the developed website. After conducting the research, based on the results of the assessment of the validation test of media experts 100.00%, material experts 98.80%, practitioners 97.91%, and students 81.24% after the average results show 94.48%, which means that that the effectiveness of the guidance website on career planning is in the category of very feasible and effective for student career planning.Keywords:   Website, Career Planning